Mitoni: Antara Budaya dan Agama (Studi Kasus Desa Air Panas Kec. Pendalian IV Koto) - Syahrul Rahman dan May Listia Pika (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
Javanese society is basically a society that still maintains traditional clutures and ceremonies, as well as any ritual related to natural events or disasters, like mitoni, pregnancy, birth, circumcision, and death. This research aims to reveal the mitoni tradition in Air Panas Village, Rokan Hulu District. focus issue in this research is divided to two categories; the history of mitoni tradition in Rokan Hulu and analyzing people level’s understanding who perform mitoni tradition. This research uses anthropology perspective by participative observation, researcher is directly involved in the mitoni event. The result showed that mitoni event in Air Panas Village was carried in and preserved by Javanese transmigrants. And there are differences mitoni tradition between muslim and other religions. Non-muslim Javanese in Air Panas Village who perform mitoni tradition just bases on tradition of Java, while muslim Java perform mitoni tradition not only based on tradition but also by reading some surahs in al-quran like surah Yusuf and Maryam.